Exploiting Klebsiella pneumoniae Arginine Deiminase: Purification, Characterization, and Selective Anticancer Activity - Jawad N. K. Makassees (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Arginine deiminase (ADI) represents a promising therapeutic enzyme for treating arginine-auxotrophic cancers by catalyzing L-arginine conversion to citrulline and ammonia, exploiting the metabolic vulnerability of cancer cells deficient in arginosuccinate synthetase (ASS). Specific Background: Colorectal cancer, ranking second in mortality and third in global incidence, demonstrates heterogeneous arginine metabolism with certain tumor subtypes exhibiting impaired ASS expression, rendering them susceptible to arginine deprivation therapy. Knowledge Gap: Despite ADI's therapeutic potential, comprehensive characterization of Klebsiella pneumoniae-derived ADI and its selective cytotoxicity against colorectal cancer remains insufficiently explored. Aims: This study isolated, purified, and characterized ADI from clinically isolated K. pneumoniae strains and evaluated its selective anticancer activity against HCT-116 colorectal cancer cells versus NCM460 normal colon cells. Results: Isolate No. 5 demonstrated optimal ADI production (12 U/mg), achieving 11-fold purification through three-step chromatographic procedures yielding 32.9 U/mg specific activity with 40.9% recovery; optimal enzymatic performance occurred at pH 7 and 37°C, with Mn²⁺ and Fe³⁺ enhancing activity (120% and 105% respectively) while EDTA inhibited it (73%), confirming metalloenzyme properties; cytotoxicity assays revealed selective anticancer activity with IC₅₀ values of 390 µg/mL against HCT-116 cells and >800 µg/mL against NCM460 cells, demonstrating 2.3-fold selectivity. Novelty: This investigation provides the first comprehensive biochemical characterization of K. pneumoniae-derived ADI with demonstrated selective cytotoxicity parameters specifically targeting colorectal cancer. Implications: These findings establish K. pneumoniae ADI as a promising selective therapeutic candidate for colorectal cancer treatment, warranting further development including PEGylation strategies and combination therapy investigations.Keywords : Arginine Deiminase, Klebsiella Pneumoniae, Enzyme Purification, Colorectal Cancer, CytotoxicityHighlight : Enzyme achieved 11-fold purification yielding 32.9 U/mg through three-step protocol. Optimal activity occurred at pH 7 and 37°C with metalloenzyme characteristics. HCT-116 cancer cells showed 2.3-fold greater sensitivity than normal colon cells.